New Strategies for Volume Control in Patients with Diabetes Mellitus, a Narrative Review - Alexandre O. Gérard; Audrey Laurain; Antoine Sicard; Diane Merino; Atul Pathak; Milou-Daniel Drici; Guillaume Favre; Vincent L. M. Esnault (MDPI AG, 2022)
Sodium is reabsorbed all along the renal tubules. The positive impacts of sodium-glucose cotransporter-2 inhibitors (SGLT2i), angiotensin receptor neprilysin inhibitor (ARNI) and mineralocorticoid receptor antagonists (MRA) on hard renal and/or cardiac endpoints calls for the role of diuretics in nephroprotection and cardioprotection in patients with diabetes mellitus to be reviewed. Here, we review: (a) the mechanisms of action of the available natriuretics; (b) the physiological adaptations to chronic loop diuretic usage that lead to increased sodium reabsorption in the proximal and distal convoluted tubules; (c) the physiology of sodium retention in patients with diabetes mellitus; and (d) the mechanisms of aldosterone breakthrough. We show the rationale for combined diuretics to target not only the loop of Henle, but also the proximal and distal convoluted tubules. Indeed, higher residual proteinuria in patients treated with renin-angiotensin-aldosterone system (RAAS) blockers portends poorer renal and cardiovascular outcomes. Diuretics are known to optimize the reduction of proteinuria, in addition to RAAS blockers, but may favor aldosterone breakthrough in the absence of MRA. The aim of our study is to support a combined diuretics strategy to improve the management of patients with diabetes mellitus and chronic kidney disease or heart failure.